Hope Project: development of mobile applications with augmented reality to teach dance to children with ASD - Romero Pazmiño, Mónica del Rocío (2022)
New ICT information and communication technologies, and specifically augmented reality (AR), are providing educators with effective strategies that allow them to be more effective in teaching-learning processes in children with ASD. This research aimed to develop an intervention plan to improve certain skills in children with ASD. Through a qualitative-quantitative, descriptive, experimental study, the Hoope software used as an innovative resource. At the end of this research, we can conclude that through augmented reality (AR) we reinforce and innovate certain teaching-learning processes, showing favorable results that show that through an intervention plan through NICT there may be positive impacts on children with ASD.